Corrosion resistance of modified amorphous cobalt alloys - O. Hertsyk; M. Tashak; N. Pandiak; A. Shalko; V. Slobodnyj (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології)
Amorphous metal alloys (AMА) based on Co have high corrosion resistance, which exceeds the durability of samples based on Fe, and also have the properties of soft magnetic materials. Therefore, new cobalt amorphous tape alloys can be used in medicine, in particular, as implants. An important indicator of AMC is the temperature and time interval of their use without a change in properties, that is, their level of stability, which depends on the chemical composition of the alloys and, certainly, on the conditions of production and use. At the same time, the properties of cobalt-based amorphous alloys can be changed by modification in various ways, in particular, by exposure to alternating magnetic fields. In this regard, electrochemical and structural studies of a number of AMAs based on Co are expedient: Co73,6Fe3,2Mn3,2Si5B15, Co73,6(Fe,Ni,Mo,Mn)5,7(Si0,2B0,8)21 and Co75,5Fe4,6Si6B16,7 original and modified in 0.9 % NaCl aqueous solution. The electrochemical characteristics of strip amorphous metal alloys Co73,6Fe3,2Mn3,2Si5B15, Co73,6(Fe,Ni,Mo,Mn)5,7(Si0,2B0,8)21 and Co75,5Fe4,6Si6B16,7 in 0 .9 % NaCl aqueous solution. For the first time, the influence of preliminary exposure in an alternating magnetic field for (0.5–3.0) h on the corrosion resistance of the amorphous Co73,6Fe3,2Mn3,2Si5B15 alloy was evaluated. The activation of the contact surface and the passivation of the outer surface of the alloy tape were established depending on the exposure, which is reflected by the corresponding change in the electrochemical parameters in a 0.9 % NaCl aqueous solution. Comparative comprehensive study of Co73,6Fe3,2Mn3,2Si5B15, Co73,6(Fe,Ni,Mo,Mn)5,7(Si0,2B0,8)21 and Co75,5Fe4,6Si6B16,7 alloys in 0.9 % aqueous solution NaCl showed that after the action of an alternating magnetic field, the difference in the final potential values of both the contact and outer surfaces of the ribbons of amorphous alloys is leveled. Research results are useful for manufacturers and consumers of amorphous materials.